Elucidating the mechanisms and mitigation strategies for six-phthalate-induced toxicity in male germ cells - Kim, Seok-Man; Kim, Yong-Hee; Han, Gil Un; Kim, Seul Gi; Kim, Bang-Jin; Moon, Sung-Hwan; Shin, Seung Hee; Ryu, Buom-Yong (Frontiers in Cell and Developmental Biology, 2024)
Phthalate esters (PAEs) are primary plasticizers and endocrine disrupting chemicals (EDCs) that are extensively used in numerous everyday consumer products. Although the adverse effects of single PAEs have been studied, our understanding of the effect of multiple phthalate exposure on male germ cell vitality remains limited. Therefore, this study aimed to investigate the collective effects of a mixture of PAEs (MP) comprising diethyl-, bis(2-ethylhexyl)-, dibutyl-, diisononyl-, diisobutyl-, and benzyl butyl-phthalates in the proportions of 35, 21, 15, 15, 8, and 5%, respectively, on differentiated male germ cells using GC-1 spermatogonia (spg) cells. As a mixture, MP substantially hindered GC-1 spg cell proliferation at 3.13 μg/mL, with a half-maximal inhibitory concentration of 16.9 μg/mL. Treatment with 25 μg/mL MP significantly induced reactive oxygen species generation and promoted apoptosis. Furthermore, MP activated autophagy and suppressed phosphorylation of phosphoinositide 3-kinase, protein kinase B, and mammalian target of rapamycin (mTOR). The triple inhibitor combination treatment comprising parthenolide, N-acetylcysteine, and 3-methyladenine effectively reversed MP-induced GC-1 spg cell proliferation inhibition, mitigated apoptosis and autophagy, and restored mTOR phosphorylation. This study is the first to elucidate the mechanism underlying MP-induced male germ cell toxicity and the restoration of male germ cell proliferation mediated by chemical inhibitors. Therefore, it provides valuable insights into the existing literature by proposing a combinatorial toxicity mitigation strategy to counteract male germ cell toxicity induced by various EDCs exposure.